Optimalisasi Persediaan Bahan Bakar Solar Pada PT. Macindo Mitra Raya Dengan Metode Economic Order Quantity (EOQ) - Andri; Rizanjani, M E; Sahari, A (Program Studi Matematika, Universitas Tadulako, 2020)
PT. Macindo Mitra Raya is a type of diesel oil (BBM) industrial company that supplies diesel fuel to full fill industrial nesercity, where one of the prices of diesel is the cost of inventory that needs to be managed. This study aims to determine the total cost of diesel fuel type inventories and determine the amount of stock of diesel fuel that is economical at PT. MACINDO MITRA RAYA through the Economic Order Quantity (EOQ) method. To calculation the number of economical orders, the formula âˆš 2ð·ð‘† ð» is used. Then to determine the total fuel inventory cost, the formula âˆš2ð·ð‘†ð» is used where D is the annual fuel order, S as the order ordering cost and H as the total ordering cost per message. From the results of the study indicate that the economical order for PT.Macindo Mitra Raya is 48,814.07 liters and the amount of inventory costs is Rp. 1,199,039,533. From the results obtained from the research conducted it has implications for the greatest efficiency in the cost of inventory of PT. Macindo Mitra Raya.